Analisis Cemaran Kapang/Khamir Pada Serbuk Simplisia Obat Tradisional - Dewi, Resmila; RM, Nur (Jurnal Farmasi Udayana; Vol. 10, No 1, Tahun 2021, 2021)
Folk remedies are of great benefit to well being and are now being used as they are easier to access. The raw materials used for such products are plant products, animal materials, mineral materials, or mixtures. Parts of plants widely used are roots, rhizomes, branches, fruits, leaves, seeds, and bark. These ingredients are used in both fresh and dry (simplicia) form. Simplicia storage under unregulated conditions will lead to the presence of different types of microorganisms, particularly mold. This research aims at examining the extent of mold/yeast contamination in the simplicity of conventional medicinal plants. The samples used in this analysis were Turmeric rhizome, Curcuma rhizome, ginger rhizome, Sambiloto leaf, and god's crown fruit. Simplicia had been collected from five Aceh Conventional Market traders. Testing sample time bar contamination using cup technique for spreading plate method on PDA media. The results showed that AKK simplicia rhizomes turmeric 46—120 colonies/grams, rhizomes Curcuma 50—96 colonies/grams, ginger rhizomes 23—43 colonies/grams, 46—100 colonies/grams of Sambiloto leaves and 43—83 colonies/grams of god crown berries. This is less than the number of mold/yeast set by BPOM (104 colonies/g).